Insights on avian life history and physiological traits in Central Africa: ant-following species have young-dominated age ratios in secondary forest - Nikolaou, Panagiotis; Krochuk, Billi A.; Rodrigues, Patricia F.; Brzeski, Kristin E.; Mufumu, Susana L.; Malanza, Silvestre E.; Tonra, Christopher M.; Cooper, Jacob C.; Wolfe, Jared D.; Powell, Luke L. (Frontiers in Conservation Science, 2025)
The Congo Basin rainforest and adjacent Lower Guinea Forest constitute the second largest tract of lowland tropical rainforest in the world. As with the rest of the continent, human population is increasing rapidly and forest degradation is ubiquitous. Forest degradation through logging has pervasive negative effects on ecosystems, but selective logging is considered less impactful than clearcutting. Recent research in Afrotropical forest shows that certain avian species and guilds are more affected by selective logging than others (e.g., specialist insectivores such as followers of Dorylus driver ants); however, the mechanisms behind these patterns are poorly known. In an eight-year mist-netting effort in Equatorial Guinea, we caught 1193 birds in primary forest and high-grade selectively logged forest to determine the effect of disturbance on six demographic and physiological measures on birds. We compared five life history and population traits for ten insectivorous species: proportion of breeding and molting birds, molt-breeding overlap, bird age, and a body mass index. We also analyzed the concentrations of the stress hormone feather corticosterone (fCORT) in five species. All three strict ant-following species (Alethe castanea, Chamaetylas poliocephala, Neocossyphus poensis), and the Muscicapid robin Sheppardia cyornithopsis had a higher proportion of first year birds in secondary forest. Furthermore, two ant-followers, A. castanea and C. poliocephala, had a higher proportion of individuals molting in primary forest. Finally, only Illadopsis cleaveri had higher body condition in secondary forest. We found no differences in breeding status, molt-breeding overlap or fCORT between forest types. Using a long-term mist-netting effort, we use measures taken from birds in-the-hand to go beyond insights from point counts alone; we gain valuable insights into the demography and physiology of Afrotropical birds occupying variably degraded lowland tropical rainforest.